Redox regulation of enzymes involved in sulfate assimilation and in the synthesis of sulfur-containing amino acids and glutathione in plants - de Bont, Linda; Donnay, Natacha; Couturier, Jérémy; Rouhier, Nicolas (Frontiers in Plant Science, 2022)
Sulfur is essential in plants because of its presence in numerous molecules including the two amino acids, cysteine and methionine. Cysteine serves also for the synthesis of glutathione and provides sulfur to many other molecules including protein cofactors or vitamins. Plants absorb sulfate from their environment and assimilate it via a reductive pathway which involves, respectively, a series of transporters and enzymes belonging to multigenic families. A tight control is needed to adjust each enzymatic step to the cellular requirements because the whole pathway consumes energy and produces toxic/reactive compounds, notably sulfite and sulfide. Glutathione is known to regulate the activity of some intermediate enzymes. In particular, it provides electrons to adenosine 5′-phosphosulfate reductases but also regulates the activity of gamma-cysteine ligase by reducing a regulatory disulfide. Recent proteomic data suggest a more extended post-translational redox control of the sulfate assimilation pathway enzymes and of some associated reactions, including the synthesis of both sulfur-containing amino acids, cysteine and methionine, and of glutathione. We have summarized in this review the known oxidative modifications affecting cysteine residues of the enzymes involved. In particular, a prominent regulatory role of protein persulfidation seems apparent, perhaps because sulfide produced by this pathway may react with oxidized thiol groups. However, the effect of persulfidation has almost not yet been explored.